Intervensi Negara dalam Moderasi Beragama melalui Kebijakan “Kampung Moderasi Beragama”: Bukti dari Kota Serang - Ima Maisaroh; Titi Stiawati; Mahpudin Mahpudin (Society, 2025)
This study examines state intervention in managing religious diversity through the Kampung Moderasi Beragama (KMB) program in Serang City, Banten. Despite the extensive promotion of religious moderation in Indonesia, limited attention has been paid to how such policies operate at the local level and how state formalization reshapes community-based pluralism. Addressing this gap, the study adopts a qualitative exploratory case study involving two urban villages (Kota Baru and Banten Lama) and fifteen key informants drawn from government institutions, religious organizations, and community groups. Data were collected between April and May 2025 through triangulated interviews, focus group discussions, and document analysis. The findings indicate that KMB functions primarily as a state-led process of formalization rather than a grassroots initiative. The dominance of state actors, the limited involvement of non-state groups, and weak intersectoral coordination render the program largely symbolic. Drawing on Althusser’s concept of the Ideological State Apparatus and Tania Murray Li’s notion of rendering technical, this study demonstrates how the state translates complex social relations into bureaucratic projects that promote narratives of harmony while marginalizing the lived realities of pluralism. Theoretically, the study contributes to critical governance scholarship by showing how state-led religious moderation can reproduce ideological control under the guise of tolerance. Practically, it highlights the need for participatory and context-sensitive governance that strengthens local ownership, interfaith collaboration, and cross-sectoral integration, enabling KMB to evolve from a performative initiative into a transformative platform for social cohesion.